The Practice of Ihya'ul Mawat as a Method of Environmental Love Education for the Community in Boresan 2 Hamlet, Balesari Village, Bansari District, Temanggung Regency - Alfin Hidayat, S.H Alfin; Joni; Muh. Baehaqi; Muhammad Syakur; Sumarjoko; Husna Nashihin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Land degradation and limited ecological awareness among communities demand environmental education approaches that integrate local and religious values. This research aims to analyze the implementation of ihya'ul mawat practice as an environmental education method for communities in Boresan 2 Hamlet, Balesari Village, Bansari District, Temanggung Regency. Using a qualitative approach with case study design, the research involved in-depth interviews with land managers, village officials, and National Land Agency officers, as well as analysis of land ownership documents. The findings indicate that communities have implemented ihya'ul mawat practices for over 30 years through transforming unproductive land into sustainable residential and agricultural areas. The experiential learning process that occurred naturally has fostered practical ecological awareness in land management, water system arrangement, and conflict resolution through deliberation. However, this practice has not been integrated with theological understanding of the concepts of khalifah, amanah, and justice in Islamic environmental fiqh. The main challenge faced is legal uncertainty of land ownership due to administrative complexity of inheritance and minimal valid documentation, resulting in certification failures despite productive land management. This research concludes that ihya'ul mawat has significant potential as a religious value-based environmental education instrument, provided that structured programs are developed integrating theological learning with land conservation practices, supported by policies addressing ownership status and active participation of religious leaders and communities in internalizing Islamic values regarding environmental preservation to achieve holistic sustainability